Seed coat-derived ABA regulates seed dormancy of Pyrus betulaefolia by modulating ABA and GA balance - Wang, Xiaoting; He, Lufang; Li, Jianzhao; Bai, Songling; Teng, Yuanwen; Hui, Wei (Frontiers in Plant Science, 2025)
Plant seeds have evolved diverse dormancy types and regulatory mechanisms to adapt to environmental conditions and seasonal changes. As a commonly used rootstock for cultivated pears, Pyrus betulaefolia faces challenges in seedling production and large-scale cultivation due to limited understanding of seed dormancy mechanisms. In this study, we report that Pyrus betulaefolia seeds exhibit non-deep physiological dormancy, with seed coats playing a pivotal regulatory role. Exogenous abscisic acid (ABA) treatment, fluridone application and seed coat bedding assay demonstrated that dormant seed coats actively synthesized ABA to inhibit embryo germination during imbibition. ABA in imbibed dormant seed coats stimulated ABA biosynthesis in embryos, leading to increased expression of genes involved in ABA biosynthesis (PbeNCED-3) and ABA-responsive (PbeABI3-1, PbeABI5-1, and PbeABI5-5). Importantly, PbeABI5-5 directly binds to the promoters of GIBBERELLIN 2-OXIDASE 3/4 (PbeGA2ox-3/4) to activate their transcription. We establish that in dormant Pyrus betulaefolia seeds, the seed coat controls embryo dormancy release through coordinated regulation of PbeABI5-GA2ox module, thereby maintaining the critical balance between ABA and GA.